PENGEMBANGAN PERANGKAT PEMBELAJARAN MODEL EKONOMI KREATIF SEBAGAI LANGKAH DALAM MEMPERSIAPKAN SISWA YANG BERJIWA ENTREPRENEUR PADA MATA PELAJARAN KEWIRAUSAHAAN KELAS X DI SMKN 7 YOGYAKARTA - Dicky Pradana; Agung Budi Luhur Wibowo; Sri Nuryanto (Pelita - Jurnal Penelitian Mahasiswa UNY, 2012)
This research is aimed to: 1) develop the Creative Economy learning model 2) to growideas and creativity of students 3) to grow students’ entrepreneurship spirit.This research used a Research and Development (R D) method. The research wasconducted from May to June 2012. The subjects were 32 students of class X of SMK N 7Yogyakarta.The data collection techniques were observation and interview. The data analysiswas qualitative and descriptive in nature to reveal the emergence of creative skills related tothe economic development of creative learning models.The results showed that: 1) Creative Economy Learning Model growing students’creativity as a step of preparing students’ entrepreneurship spirit based on the results of thevalidation results of the instruments experts or specialists as a whole was good. The scoreobtained by the model instrument was 3.81 with a very good criteria. 2) the score of thesyllabus was categorized as good and the score was 3.13. the score of the lesson plan was3.14 and was categorized as good. 3) The model of syllabus and lesson plan were proven togrow the students’ creativity and entrepreneurial spirit. Based on the observations, it can beconcluded that the development of the Creative Economy learning model held in class X ofSMKN 7 Yogyakarta showed that students were able to nurture the creativity that wouldgrow their entrepreneurial spirit. It was proven with the result showing that there were 24students reached the level of being creative, 5 students achieved the level of being quitecreative, and three students achieved the level of less creative. The average grade obtainedfor creativity was 15.3; therefore, it was categorized as creative.Keywords: Creative Economy, Entrepreneur, Students